Pulmonary Vein Stenosis: Case Report and Literature Review - R Amin; S Kwon; Y Moayedi; N Sweezey (Canadian Respiratory Journal)
BACKGROUND: Pulmonary vein stenosis is a rare cause of pulmonary hypertension, with variable onset and presentation. One or more of the four pulmonary veins can be primarily or secondarily affected. A five-month-old girl presented with respiratory distress, lethargy and cyanosis requiring intubation.